Identification of parthenocarpic genotypes of Cucurbita pepo L. type Grey Zucchini - Ramìrez Zavala, Luis Fernando; Esteves Rangel, Daniel; Mireles Arriaga, Ana Isabel; Hernández Ruiz, Jesùs; Ruiz Nieto, Jorge Eric (Acta Universitaria, 2022)
Curcubita pepo type zucchini is an important vegetable in the Bajío region; however, its production is affected by the reduction of the populations of bee pollinators and the effect of the environmental alterations on its reproductive habits. Therefore, it is fundamental to identify parthenocarpic genotypes capable of generating fruits without any fecundation or loss of their agronomic traits. The aim of this study was to identify parthenocarpic genotypes of Cucurbita pepo type Grey Zucchini. The evaluated genotypes derived from the cross of six parent lines and two consecutive cycles of self-pollination. The genotypes were grown under controlled conditions, identifying 16 parthenocarpic genotypes. Genotypes GZS193, GZS194, GZS301, GZS148, and GZS171 presented most of the desirable traits; hence, they could be used as parents in future crossing assays to accumulate all the traits in a single genotype keep the parthenocarpy.